Google Apps meets Common Core - Graham, Michael J. (Corwin, a SAGE Company, 2013)
Enhance your curriculum and launch a stress-free implementation of the Common Core's required technology components with Google's suite of free, easy-to-use educational tools. This book shows you how to design robust lessons that help students meet and exceed Common Core requirements to think critically, problem solve, research, collaborate, and create original documents to publish on the web.